2009
DOI: 10.1002/jsfa.3540
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of Korean black raspberry wines and their apoptotic effects on cancer cells

Abstract: BACKGROUND: The objective of the study was to determine the antioxidant activities of Korean black raspberry concentrate (KBR: Rubus coreanus Miq.) and Korean black raspberry wine concentrates (KBRW-1 and KBRW-2) using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. The apoptotic effects of the KBRW concentrates on various cancer cells were also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
4
10
0
1
Order By: Relevance
“…Recently, based on the information of health beneficial effects of bokbunja, the growth area and the harvest quantity in South Korea have rapidly increased resulting in various bokbunja products, such as juices and concentrates, rice cakes, vinegar, and dietary supplements. Several studies have shown that bokbunja fruit and wine are positively related with various physiological functions, including antioxidative , anti-inflammatory (Lim, Hwang, & Shin, 2012;Yang et al, 2007), anticancer (Jung et al, 2009), anti-high cholesterol (Lee et al, 2015), and prevention of the memory impairment (Choi, Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on the information of health beneficial effects of bokbunja, the growth area and the harvest quantity in South Korea have rapidly increased resulting in various bokbunja products, such as juices and concentrates, rice cakes, vinegar, and dietary supplements. Several studies have shown that bokbunja fruit and wine are positively related with various physiological functions, including antioxidative , anti-inflammatory (Lim, Hwang, & Shin, 2012;Yang et al, 2007), anticancer (Jung et al, 2009), anti-high cholesterol (Lee et al, 2015), and prevention of the memory impairment (Choi, Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] These RCM constituents have been shown to exert diverse functional effects, including anti-osteoporosis, anti-inflammation, and anti-carcinogenesis. 10,11) Anti-carcinogenic functions of RCM are suggested to act partly by inducing DNA damage, 12) activating apoptosis, 13) and reducing angiogenesis. 14) Sanguiin H-6 extracted from RCM has been shown to decrease angiogenesis in endothelial cells via the inhibition of vascular endothelial growth factor receptor-ligand binding.…”
mentioning
confidence: 99%
“…Liu 그러나 국내산 나무딸기류에 대한 선행 연구들은 과일이 나 씨앗의 일반성분과 화학적 특성만을 분석하였으며, 항산 화능과 생리활성에 대해서는 일반적으로 보급되는 소수의 품종에 한정되어 수행되었다 (7,9,14). 본 연구에서는 국내에 서 재배한 다섯 종류의 나무딸기류 과일의 추출에 있어서 씨앗성분의 혼입이 항산화 성분 및 항산화능에 미치는 영향 을 분석하고, in vitro 모델을 이용하여 각 추출물의 NO 소거 능(RAW264.7)과 암세포(HT-29, KATO …”
unclassified